2002
DOI: 10.1183/09031936.02.00051802
|View full text |Cite
|
Sign up to set email alerts
|

Pleural-fluid myeloperoxidase in complicated and noncomplicated parapneumonic pleural effusions

Abstract: The diagnostic accuracy of myeloperoxidase (MPO) in pleural fluid, for differentiating between complicated and noncomplicated parapneumonic pleural effusions (PPE) evaluated prospectively.Seventy patients aged w18 yrs with PPE (36 complicated and 34 noncomplicated) were studied after admission to a tertiary referral teaching hospital. MPO concentration was measured in plasma and pleural fluid using a double-antibody competitive radioimmunoassay.The concentrations of MPO in complicated and noncomplicated PPE we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…Alemán et al [15] reported that a pleural fluid level of neutrophil elastase higher than 3500 mg/l identified two-thirds of CPPEs misclassified with pleural fluid pH or glucose. The same group [16] found that a pleural fluid myeloperoxidase above 3000 mg/l also helped to differentiate between nonpurulent CPPE and UPPE (AUC 0.912).…”
Section: Neutrophil-derived Enzymesmentioning
confidence: 86%
“…Alemán et al [15] reported that a pleural fluid level of neutrophil elastase higher than 3500 mg/l identified two-thirds of CPPEs misclassified with pleural fluid pH or glucose. The same group [16] found that a pleural fluid myeloperoxidase above 3000 mg/l also helped to differentiate between nonpurulent CPPE and UPPE (AUC 0.912).…”
Section: Neutrophil-derived Enzymesmentioning
confidence: 86%
“…Several biochemical markers such as myeloperoxidase, complement activation product SC5b-9 (S-protein C5b-9 complex) or CRP (C-reactive protein) have been proposed to assist decision-making regarding clinical management. Specifically, in the study of Alegre et al [34], pleural fluid myeloperoxidase at a cut-off point of 3000 lg L )1 was found to be the marker that best differentiated CPPE and UPPE (sensitivity, 87AE5%, specificity, 85AE1%; AUC = 0AE91). Furthermore, Vives et al [31] reported 100% sensitivity, 100% specificity and an AUC = 0AE89 of pleural complement activation product SC5b-9 for differentiating CPPE from UPPE when a cut-off point of 1500 lg L )1 was used.…”
Section: Discussionmentioning
confidence: 97%
“…However, biomarkers that provide information for the development of complicated parapneumonic effusions or empyemas may provide additional information to the attending physician in order to facilitate treatment decisions. Several biochemical markers such as myeloperoxidase [36], TNF-α [21] or C-reactive protein [37] have been proposed to assist decision-making regarding clinical management. In the present study we examined the diagnostic accuracy of MMPs for the differentiation between UPPE and CPPE.…”
Section: Discussionmentioning
confidence: 99%